Comparison of intravenous regional anaesthesia with lidocaine and ropivacaine in dogs - Hadi Imani Rastabi (Wiley, 2021)
Abstract The present study was designed to compare the effects of lidocaine and ropivacaine in intravenous regional anaesthesia (IVRA) in dogs. Twelve adult male dogs were used. Under isoflurane anaesthesia, exsanguination was performed in the target forelimb. Then, a blood pressure cuff was encircled around the limb proximal to the elbow joint with a pressure of approximately 150 mmHg above the mean arterial blood pressure. The animals then received one of the two treatments of lidocaine (3 mg/kg) or ropivacaine (1.5 mg/kg) with a final volume of 0.6 mL/kg into the cephalic vein. After 60 min, the anaesthesia was disrupted and the tourniquet was removed using intermittent opening (30 s) and closing (5 min) manner for three times. The results revealed that at 20 and 30 min after the initiation of IVRA, the dogs in ROP showed higher analgesia than LID. A leakage under the tourniquet during IVRA was detected. Tremor and hypersalivation were observed after tourniquet removal in some dogs. It was concluded that ropivacaine might provide a higher quality of anaesthesia than lidocaine in IVRA in dogs. The development of local anaesthetic toxicity is a major concern and should be considered at the time of tourniquet removal.